Pengaruh Promosi dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Khimaruti.Store - Iin Kardilatul Munawaroh, (Jurnal Publikasi Ilmu Manajemen, 2025)
This study aims to find out how much promotion and product quality affect the purchasing success of khimaruti.store consumers. This research method uses a quantitative method. This population and sample were taken from 900 khimaruti.store consumers using the slovin method. So far, data was obtained for 90 respondents. The data collection technique was carried out by observation and questionnaire. The data collection technique was carried out by observation and questionnaire. The results of this research are known that the variable Promotion (X1) Towards Consumer Purchase Decision (Y) was obtained with a value of r calculation t > t table of 10,720 > 1,988. So the hypothesis that states that Promotion has a positive and significant effect on Consumer Purchase Decisions. In the variable Product Quality (X2) to Consumer Purchase Decision (Y) of khimaruti.store product with a value t calculated > t table of 14,872 > 1,988.